Video games, frustration, violence, and virtual reality: Two studies. (11th June 2021) - Ferguson, Christopher J.; Gryshyna, Anastasiia; Kim, Jung Soo; Knowles, Emma; Nadeem, Zainab; Cardozo, Izabela; Esser, Carolin; Trebbi, Victoria; Willis, Emily
Abstract : The degree to which the content of video games influences aggression continues to be debated in the scholarly literature. The current article includes two studies, one of which replicates one study from Przybylski et al . (2014, J. Pers. Soc. Psychol ., 106, 441) and the other which extends related concepts into virtual reality. In the first study, two versions of Tetris were examined, differing in levels of difficulty. In the second study, participants played virtual reality games which differed in regard to difficulty and violent content. Difficulty increased hostility in the second study but not the first. Violent content influenced neither hostility nor aggressive behaviour. Results partially supported the frustration theory of aggression, but not theories of violent content effects. Implications for the field are discussed.